Tradisi dan adat istiadat Samawa - Zulkarnain, Aries, 1948- (Yogyakarta, Indonesia : Ombak, 2011)
Rites and ceremonies of Samawa ethnic people in Sumbawa Island, Nusa Tenggara Barat.
Includes bibliographical references (page 236-237) and index.
Keywords: Sumbawa (Indonesian people) -- Social life and customs; Sumbawa (Indonesian people) -- Rites and ceremonies